1990
DOI: 10.2118/19392-pa
|View full text |Cite
|
Sign up to set email alerts
|

Rock/Fluid Interactions of Carbonated Brines in a Sandstone Reservoir: Pembina Cardium, Alberta, Canada

Abstract: Summary When CO2 is injected into petroleum reservoirs it forms carbonic acid in the brine phase and interacts with reservoir rock. Flow tests were performed by continuously circulating CO2-saturated brines through Cardium formation cores. All the cores initially showed a large drop in permeability, after which permeability rose steadily but did not regain its initial value. Microscopic examination of the cores indicated that fines had been released and had migrated toward pore throats, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 18 publications
1
63
0
1
Order By: Relevance
“…Other studies have observed reduced injectivity in some calcareous sandstone and carbonate formations (Henry, and Feather, 1981, Ross, et al 1982, and Sayegh et al, 1990. Also, the tendency of scaling of production water during CO 2 injection has led some researchers to investigate the inorganic geochemical aspects of CO 2 reservoir interactions (Bowker andShuler, 1991, Shuler et a.1991).…”
Section: Task 41 Establish Physical Property Correlationsmentioning
confidence: 99%
“…Other studies have observed reduced injectivity in some calcareous sandstone and carbonate formations (Henry, and Feather, 1981, Ross, et al 1982, and Sayegh et al, 1990. Also, the tendency of scaling of production water during CO 2 injection has led some researchers to investigate the inorganic geochemical aspects of CO 2 reservoir interactions (Bowker andShuler, 1991, Shuler et a.1991).…”
Section: Task 41 Establish Physical Property Correlationsmentioning
confidence: 99%
“…A geostatistical study of small-scale heterogeneity is more difficult because of the more subtle differences in sedimentation types within eolian sandstones. Authors who have done similar work on eolian and other types of sediments (Grant et al, 1994 andProsser andWilliams, 1993) (Ross et al, 1981;Omole and Osoba, 1983;Sayegh et al, 1990). However, carbonate scale formation and corrosion, which accompany CO2 flooding, are costly.…”
Section: Conclusion Of Statistical Analysis Of Permeability Heterogementioning
confidence: 99%
“…Assuming that changes in permeability should be due to dissolution or precipitation of carbonate minerals at the pore throats, Omole and Osoba concluded that CO2 flooding into carbonate reservoirs would result in the dissolution of carbonate minerals near injection wells and precipitation of them at production wells. Sayegh et al (1990) carried out CO2 flooding experiments at 45°C and 1.38xl07Pa (138 bars) using sandstone cores from the Pembina Cardium oil field, Alberta, Canada. They observed that the permeability of cores rapidly decreased at the early stage of the experimental runs and then increased gradually throughout the remainder of the experiment.…”
Section: Conclusion Of Statistical Analysis Of Permeability Heterogementioning
confidence: 99%
“…Injected CO 2 dissolved in formation water to produce carbonic acid which will react with the reservoir rock [10] [11] [12]. The porosity and permeability of the reservoir [13] [14] [15] [16] [17], the wettability of the rock surface and the characteristics of the crude oil will be changed by the reaction between carbonic acid and the rock [18] [19], which will affect the efficiency of CO 2 flooding and geological sequestration of CO 2 [20] [21] [22]. And the carbonate minerals in the reservoir can especially easily react with CO 2 and water to affect reservoir property.…”
Section: Introductionmentioning
confidence: 99%